INNOVATION STRATEGY ELABORATION AND IMPLEMENTATION IN COMMERCIAL ORGANIZATION - A. V. Sayapin (Стратегические решения и риск-менеджмент)
The article analyzes the meaning of company's innovation strategy which is considered as one of the functional strategies. It examines positive role of company’s motivate environment for innovation ideas creation and realization. The article explores number of case studies where effective influence of motivate environment on the whole company’s innovation activity is proved.